Transforming the Picturebook “Little Walrus Gets Glasses” into a Dance Dramatization - Jurgec, Ana Tina (Trideset let literarne nagrade večernica, 2026)
The article is based on the theory of multimodality, which emphasizes that meaning is created through the interaction of different semiotic modes, such as language, image, movement, space, and sound. As a multimodal art form, the picturebook enables the transformation of meaning from a verbal-visual medium into other artistic expressions, including dance dramatization. The article examines the process of transforming the picturebook Little Walrus Gets Glasses by Peter Svetina, illustrated by Mojca Osojnik, into a dance dramatization. The study explores how verbal and visual elements are transformed into movement and how linguistic, visual, gestural, spatial, and auditory modes interact within the performance. The analysis is based on a qualitative approach and reflection on the creative process. The findings show that dance dramatization represents a complex multimodal artistic form in which movement assumes a central narrative and interpretative role, transforming the original picturebook into a new movement-based artistic expression.